AACO technique for solving multiobjectives in electrical distribution system - P. Ravi Babu; Srivani Molughu (Institute of Advanced Engineering and Science, 2019)
The multi objectives in electrical distribution system are service restoration and minimization of Ohmic losses. These objectives can be achieved by artificial ant colony optimization through reconfiguration. Service restoration is also a major aspect for reliable service. If any fault occurs in the system, faulted zone is isolated from healthy system. This originates discontinuity in power supply. To maintain the continuity in power supply there is a necessity to provide service to these loads from adjacent healthy feeders through reconfiguration without infringement of radiality, load balance and critical parameters. In distribution system Ohmic losses are 30 to 40 percent. In order to minimize these losses, there is a need for reconfiguration of the system and perform the power flow analysis to get bus voltages, branch currents and power losses (i.e. real or Ohmic or copper loss and reactive power loss). A direct load flow analysis is adopted in the proposed work. In this paper four feeder test system used for service restoration and IEEE 33 bus, IEEE 69 bus test systems for minimization of Ohmic losses have been obtained.